PACE MAKERS OF DEVELOPMENT WOMEN IN INDIAN HISTORY: PAST-PRESENT— A CRITICAL REVIEW - Shrimati Das; M.M. Dhalayat (Humaniora, 2013)
No matter how the world changes, no matter what country and social system people are in, no one can deny women’s importance in history. But it does not mean that women are always treated well and fairly, and the women’s role in history has undergone numerous changes. In the past few decades women were considered to be a part of wealth and property. She used to be sold and purchased like any property or cattle. Till recently women were treated on different footing/pedestal, ‘depriving’ them of their rights but ‘reminding’ them of their duties. But with the changing times, the role of women in India has changed from child bearing to rearing to bread earner. Thus the new cultural milieu is making it inevitable for them to face the emerging reality in contemporary Indian society. This article is an attempt to throw light on the status of women in India from past to the present. It also tries to explain the position of women on the basis of socio-economic- political empowerment. Throughout the Indian history the double standard regarding the status of women is evident. In Literature and Religion of India, women are highly placed. But in the domestic, political and economic scenario, women occupy a lower status and are subjected to discrimination and exploitation. Women’s role in India has been changing over the years and women are now emerging from the past traditional set-up to a new era of freedom and rights. Role of women in modern India can be called as ‘phenomenal’. The fortunes of Indian women from the past to the present, is worth following. Indian women who were once considered to be the masters in the art of home making are now considered to be the ‘forces that shape the country’, which is the size of a continent.